Child and teenager participation in the Province of Alicante: The use of participatory budgets as an empowering dynamic - Abellán López, María Ángeles; Pardo Beneyto, Gonzalo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article focuses on the study of various experiences based on dynamics of participatory budgets and aimed at children and adolescents. This research collected data from the main participatory experiences in the Alicante Province during the 2015-2022 period through a survey and a search for related documentation. The data from the municipalities have been processed through the MAXQDA program. Among the main results, it is possible to highlight the different perceptions that the participants have of the concept and the need to delve into instruments of this nature.